Smart vending machine counter using IOT - Ali Ali, Athir Jaafar (2020)
The availability of vending machine has become imperative for human as they depend on it to access products conveniently. Customer satisfaction and minimizing the expenses is one of the biggest challenges to the company by working on all details of the vending machine. Keeping the vending machine always full with the stock of inventories is hard to keep because the distances between the vending machines and the supplying company needs huge expenses, so it affects the customer satisfaction when it runs out of stock. For the sake of obtaining both customer satisfaction and minimizing the expenses is by keeping the vending machine always full of its products stock as well as and reducing the expenses we need to work on smart vending machine. This project presents smart vending machine counter using IOT. The developed system count the sales of the products in the vending machine and stores the data in an IOT platform called ThingSpeak platform in real-time. This prototype system consists of two parts namely: hardware and software. The hardware part consists of ESP8266 NodeMCU, IR proximity sensor, DC motor. The software part on the other hand consists of ThingSpeak platform, Scetchware and Wirepusher. The results can be shown the real-time sales of each product in the vending machine (VM) prototype. The prototype was built and tested to collect data for 12 days and analyse these data. Moreover, it shows the development of vending machine mobile application that is used for monitoring as well as getting notifications or alerts when the products is about to be out of stock. Finally, the project design and built conclusion has successfully been able to monitor the stock inventory (SI) in the vending machine in real time so as to reduce expenses and enhance the customer satisfaction. It is considered a novelty that the smart vending machine counter was able to achieve all the targeted objectives and provide an effective smart counting system using IOT technologies an the innovations of Think speak interchangeability with scetchware and wire usher systems. The project was successful in managing to integrate, embed and synchhrnoize all the IOT technologies alongside IR sensor technologies in the form of fully integrated sophisticated smart system. Our system and project modality will be very beneficial to all the manufactures and producers of vending machines industries and businesses.